Fungsi dan Peran Konseling Islam Dalam Pendidikan - Abdurrahman, Abdurrahman (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This article discusses the functions and important role of Islamic counseling in education. The method used is descriptive analysis, by exploring all the resources related to Islamic counseling as a means of education. Islam is the Shari'a of Allah for humans, with the provision of the Shari'a that humans worship as a form of realization to serve Allah SWT. In order for humans to be able to bear and realize the great mandate, the Shari'a requires practice, development and formation known as Islamic education. Of course there will be no realization of Islamic law without any effort to forge themselves, and for that we need an educational role to be introduced from generation to generation. Islamic counseling greatly contributes greatly to education. Islam as a religion full of divine values will give a positive value in the world of education. That way, Islamic counseling plays an important role in the world of education. Humans who basically really understand the values of Godhead that are within them.